Diagnóstico da esquistossomose mansoni em área de baixa endemicidade através do POC-CCA : comparação com outros métodos e avaliação pós-tratamento - Leal, Joames Kauffimann Freitas (2014)
The detection of circulating antigens has been an alternative to the problems with the diagnosis of schistosomiasis, the disease that affects approximately 200 million people in 74 countries, worldwide. A newly developed immunoassay to detection of CCA (POC-CCA, point- of-care) in urine have shown high sensitivity and specificity for the schistosomiasis study . However, the most of all studies was carryed in areas of high endemicity in Africa, and there is a need for more studies to verify this test’s diagnostic accuracy in low endemic areas and their geographical differences. Our aim was to evaluate the effectiveness of POC-CCA as diagnostic of schistosomiasis, comparing it with a parasitological method and a linked immunosordent method and to evaluate how the POC-CCA behaves after chemotherapy, in residents of an area of low endemicity. The study was conducted for six months in Banananeiras, a village in Capistrano, Ceará, Brazil. Stool (Kato-Katz), blood (SWAP-ELISA) and urine (POC-CCA) were used to perform the tests. The community had 297 inhabitants, 285 of these agreed to participate in the study, and 258 (190 adults and 68 children) gave the three samples. Before treatment, the prevalence of S. mansoni, as determined by triplicate Kato-Katz, POC-CCA considering “P=trace”, POC-CCA considering “N=trace” and SWAP-ELISA was 1,6%, and 40,7%, respectively. The Kato-Katz method had a sensitivity lower than was expected and SWAP-ELISA showed up discordant results. Nevertheless, the results of our study show high sensitivity and specificity of POC-CCA, however, the gold standard chosen for the comparisons may have influenced the results. The patients were treated and re-evaluated by immunoassay, three and six weeks after treatment. POC-CCA used in the post-treatment evaluation and when we compared “P=trace” against “N=trace”, we found a higher percentage of individuals that became negative, considering “P=trace”; although all adults had negated, considering N=trace. Although, six weeks proved to be the best time for reassessment after treatment.